2016
DOI: 10.1073/pnas.1604936113
|View full text |Cite
|
Sign up to set email alerts
|

Sensing and signaling of oxidative stress in chloroplasts by inactivation of the SAL1 phosphoadenosine phosphatase

Abstract: Intracellular signaling during oxidative stress is complex, with organelle-to-nucleus retrograde communication pathways ill-defined or incomplete. Here we identify the 3′-phosphoadenosine 5′-phosphate (PAP) phosphatase SAL1 as a previously unidentified and conserved oxidative stress sensor in plant chloroplasts. Arabidopsis thaliana SAL1 (AtSAL1) senses changes in photosynthetic redox poise, hydrogen peroxide, and superoxide concentrations in chloroplasts via redox regulatory mechanisms. AtSAL1 phosphatase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 83 publications
(98 reference statements)
3
158
0
Order By: Relevance
“…Oxidative stress during drought alters chloroplast redox poise to induce a 30-fold PAP accumulation via redox regulation of SAL1 (Estavillo et al, 2011; Chan et al, 2016b). PAP accumulation could activate its downstream signaling through XRNs to transcriptionally up-regulate multiple ABA/Ca 2+ signaling proteins that are normally lowly expressed, and this includes four CDPKs that can activate SLAC1 in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress during drought alters chloroplast redox poise to induce a 30-fold PAP accumulation via redox regulation of SAL1 (Estavillo et al, 2011; Chan et al, 2016b). PAP accumulation could activate its downstream signaling through XRNs to transcriptionally up-regulate multiple ABA/Ca 2+ signaling proteins that are normally lowly expressed, and this includes four CDPKs that can activate SLAC1 in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, phytopathogenic bacteria, including Pseudomonas syringae pv tomato DC3000 (Pst), target photosynthetic electron transport at photosystem II to inhibit CO 2 assimilation and ROS production in an ABA-dependent manner (Rodr ıguez-Herva et al, de Torres Zabala et al, 2015). Under high light or drought, perturbations in the Calvin cycle generate ROS and chloroplast-nucleus retrograde signals such as methylerythritol cyclodiphosphate (MEcPP; Xiao et al, 2012) and 3 0 -phosphoadenosine-5 0 -phosphate (PAP), a by-product of sulfur metabolism (Chan et al, 2016). Oxidation-mediated inactivation of SAL1 phosphoadenosine phosphatase generates PAP to confer drought tolerance (Chan et al, 2016).…”
Section: High Light and Uv-b Stressmentioning
confidence: 99%
“…In contrast, operational control enables plastids to regulate the expression of nuclear genes in response to environmental cues, enabling plants to optimize photosynthetic performance. To date, several molecules, including reactive oxygen species (Karpinski et al, 1999;Wagner et al, 2004), methylerythritol cyclodiphosphate (Xiao et al, 2012), and 39-phosphoadenosine-59-P (Estavillo et al, 2011;Chan et al, 2016), have been shown to participate in operational control.…”
mentioning
confidence: 99%